ANALISIS TAX PLANING DALAM UPAYA MINIMALISASI HUTANG PAJAK PADA INDUSTRI KECIL MENENGAH DI KOTA MEDAN - Irawan, Irawan (JURNAL PERPAJAKAN, 2024)
The purpose of this study is to find out whether the application of tax planning in Small and Medium Industries is appropriate according to the Tax Law. In this study, a descriptive research approach is used, which is a research to compile, classify, interpret and interpret data so as to provide an overview of the problem of analysis of the effectiveness of operational cost control. The data analysis technique uses the descriptive method of the Accounting approach. Based on the results of data analysis and discussion, it can be found that the tax filing carried out by the company is not in accordance with the applicable tax regulations, where the company does tax planning without taking advantage of the applicable tax regulations. The company has made efforts to implement tax planning on the welfare costs of its employees, and efforts to minimize its tax burden are considered not optimal because the company has not utilized in-kind costs as recognized expenses according to taxes. The cost of the PKP deduction is only limited to the cost of health benefits and transportation allowances, while employee meal allowances and work clothes cannot be deducted as tax objects.